PENINGKATAN KEMAMPUAN BACA TULIS PESERTA DIDIK PADA MATERI AL-QUR’AN SURAT AT TIN MELALUI METODE DEMONSTRASI DI KELAS IX.7 SMP NEGERI 10 KOTA BEKASI - ., Rapisah (Program Studi Pendidikan Agama Islam, Fakultas Agama Islam UNISMA Bekasi, 2016)
The purpuse of this research is to improve reading and writing skills of the Al- Qur?an Surah At-Tiin through demonstration method in the class IX.7 SMP Negeri 10 Bekasi. The subjects were students of class IX.7 SMP Negeri 10 Bekasi as 42 students. The method used in the class action research consisted of two cycles. The technique of collecting data through observation, tests, interview, and discussions. The results of the research data showed that: (1) the results of the observation that through the method of demonstration student behavior have increased positive, (2) Results sheets journals that students learning attitude of students during each cycle already has increased quite good, (3) The results of the observation sheet on teacher performance during the learning that teachers have been able to apply the method of demonstration quite good start of stages of preparation to the presentation, so learning through demonstration method had a positive impact on behavior and students understanding of the subject matter more increases, (4) that an increase to improve reading and writing skills of the Al-Qur?an Surah At-Tiin between before being given treatment with after treatment is given through the demonstration method, cycle II as 95,24% student have had reading adn writing skill of the Al-Qur?an Surah At-Tiin in current category. It is concluded that learning through demonstration method can improve learning outcomes Islamic religious education especially reading and writing